Changes in Mindfulness following Repetitive Transcranial Magnetic Stimulation for Mood Disorders. (December 2013) - Leong, KaWai; Chan, Peter; Grabovac, Andrea; Wilkins-Ho, Michael; Perri, Maria
Objective: Mindfulness practices are associated with changes in different cortical regions, including the dorsolateral prefrontal cortices (DLPFCs). Our study sought to examine how an index course of repetitive transcranial magnetic stimulation (rTMS) over the DLPFC improved components of mindfulness as assessed by Baer's Five Facet Mindfulness Questionnaire (FFMQ) and the Experience Questionnaire (EQ). Method: Our preliminary study is a retrospective chart review of 32 patients who had undergone an index course of rTMS for major depressive episode between 2009 and 2012. The following information was collected prior to rTMS: patient demographics, diagnosis, and age of onset of primary diagnosis. The following information was collected prior to and after rTMS: 21-item Hamilton Rating Scale for Depression (HRSD) scores, Patient-Health Questionnaire (PHQ-9) scores, Generalized Anxiety Disorder 7-item (GAD-7) scale scores, FFMQ scores, and EQ scores. Results: Following rTMS, results showed statistically significant decreases in HRSD, PHQ-9, and GAD-7 scores. There was significant improvement in the nonreactivity to inner experience subscale of the BFFMQ and in the decentring subscale of the EQ. Subgroup analysis between patients who did not improve on the HRSD by 50% or more following rTMS and those who did revealed no baseline difference in mindfulness. There was significant improvement in the decentring subscale of the EQ in both subgroups. Conclusions: Our study provides preliminary data that rTMS may be associated with improvement in some components of mindfulness, independently of changes in depression.